House of cards : monsters in politics - Taïeb, Emmanuel (Intellect Books, 2022)
Exploration of the idea that House of Cards sets an alternate political world, where the leader is a ferocious animal, a political field overtaken by monsters who remain true to their fundamental nature or try to master their bloodthirsty instincts. But can we really think that the elected men and women are so different from their constituents?